Chasing ephemerality: Notes on doctoral mentoring and artistic collaboration. Issue 3 (1st December 2016) - Hafeli, Mary; Koo, Sohee
In this article, we explore our experiences and shifting positions as doctoral mentor and mentee, co-mentors, and collaborators over the course of one semester. We use duography (Diamond and Mullen 1996) as an analytical approach to reveal the convergence of separate perspectives and voices as we examine both the evolution of dissertation research questions and a shared studio project – highlighting mentoring and collaborative practices that stretch, blur, and morph into one another. Writing together is a transparent way of discovering what we know or have learned, and of mentoring and being mentored within and about the writing process itself. Our account describes both the co-construction of research and the ways in which our collaborative research and studio practices changed, and changed us, over time.